Regulación económica y países en vía de desarrollo: diálogo con Robert Baldwin - Vargas Guevara, Erick E. (2015)
Regulation   and   regulatory   agencies   have   aninfluence on the economy and on the legal system ofa country. In this context, which are the challengesof regulatory agencies in developing countries, forexample, Peru? What is their relation with foreign investment? In a context of financial crisis, which isthe role that these agencies should play?THĒMIS-Law Review had the opportunity to briefly interview one of the more recognized and consulted experts in Regulation, who provided answers to the questions indicated above.